Kreativitas Guru MI Nurul Hidayah dalam Meningkatkan Minat Belajar Siswa untuk Membentuk Siswa Berprestasi - Della Noviana; Muhammad Dahlan Rabbanie; H.M Kholil Nawawi (Jurnal Gentala Pendidikan Dasar, 2020)
ABSTRACT This study aims to increase the interest in learning by the creativity of teacher in 4th grade MI Nurul Hidayah Bogor in the academic year 2018/2019. This research was a qualitative descriptive method to approach case studies. Data retrieval techniques use interview, observation, documentation and questionnaire techniques. Creativity of teacher invented by researchers is like creativity found on how to teach in a fun way, planning field trip, and mentoring the contest in MI Nurul Hidayah of course increases the interest in students learning because when teachers teach with passion and creativity, such enthusiasm and creativity certainly spreads to student who can eventually develop the interest of student’s learning well. This thing, evidenced when a student study is done it shows love for the passage taught by the teachers of students with a high interest in learning, a boisterous class atmosphere is greatly implied when researchers observe in the classroom during the course of the period. The researchers came to see that with teacher creativity, a great atmosphere of learning is done well so that students can easily receive the lessons that are taught after students can easily receive the lessons. The student will be so pleased with the attainment that a high interest in learning will reemerge on a daily basis, as each student feels self-satisfaction with the result of research, the researchers can arrive at conclusions and implications that a teacher’s creativity could certainly increase the student in a way that would shape a student’s achievement.